Enhancing the Mechanical Characteristics of Eco-Friendly Composite Materials: Taguchi and RSM Optimization - Khalissa Saada; Salah Amroune; Ahmed Belaadi; Moussa Zaoui; Ibrahim M. H. Alshaikh; Djamel Ghernaout (Journal of Natural Fibers)
Green composites consisting of renewable or biodegradable materials are becoming more popular as environmental awareness of global waste issues grows. Among them, natural composites made of polymers have proven to work exceptionally well because of their high strength, rapid breakdown after disposal, and simplicity in processing using standard techniques. In particular, competitive mechanical performances have been demonstrated by green composites having a polymer matrix reinforced with sisal, luffa, and maize fibers at different fiber percentages of 10%, 15%, and 25%. The tensile characteristics of polymer composites reinforced with these fibers are optimized in this study by the application of Taguchi and response surface methodology. By assessing characteristics such as section size, fiber content, and fiber type simultaneously, the study attempts to produce optimal biocomposite qualities, which are then experimentally tested. Tensile tests show considerable gains: the biocomposite containing 15% corn fiber showed a 21.04% increase in tensile strength. Similarly, sisal, luffa, and corn fibers all showed notable improvements in Young’s modulus, with the biocomposite showing 22.77%, 31.77%, and 20.25% increases, respectively.